2020
DOI: 10.5716/wp20026.pdf
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal value chains in Kenya: a 20-year synthesis

Abstract: PDFThe titles of the Working Paper Series are intended to disseminate provisional results of agroforestry research and practices and to stimulate feedback from the scientific community.Other World Agroforestry publication series include Technical Manuals, Occasional Papers and the Trees for Change Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Most participants preferred firewood to charcoal, stating that using firewood is not only their cultural heritage, but also a more affordable option. Use of charcoal seems to be reserved for the comparatively more well-off urban population (QMM 2001), as is the case in many parts of Africa (Kersten et al 1998;Tabuti et al 2003;Arnold et al 2006;Woollen et al 2016;Ndegwa et al 2020) and southeast Asia (Sovacool 2013; Win et al 2018). As one of the Mandena participants disclosed, it is not uncommon for charcoal producers to sell all the charcoal they make to increase their income, and use firewood themselves.…”
Section: Construction Materials Firewood and Othermentioning
confidence: 99%
“…Most participants preferred firewood to charcoal, stating that using firewood is not only their cultural heritage, but also a more affordable option. Use of charcoal seems to be reserved for the comparatively more well-off urban population (QMM 2001), as is the case in many parts of Africa (Kersten et al 1998;Tabuti et al 2003;Arnold et al 2006;Woollen et al 2016;Ndegwa et al 2020) and southeast Asia (Sovacool 2013; Win et al 2018). As one of the Mandena participants disclosed, it is not uncommon for charcoal producers to sell all the charcoal they make to increase their income, and use firewood themselves.…”
Section: Construction Materials Firewood and Othermentioning
confidence: 99%
“…CPAs, were, before the ban, responsible for sustainable charcoal production that did not degrade the forest cover and coordinated reforestation activities and development of conservation plans for sustainable charcoal production. Consumption is not forbidden and hence considerable charcoal production and use still continues even after the ban in 2018 [32]. Since charcoal production and trade is informal and partly banned, precise production or consumption figures are not easily available.…”
Section: The Study Regionmentioning
confidence: 99%
“…Value chains in the charcoal sector have been well studied by FTA scientists, who have demonstrated that the sector provides critical employment and income for multitudes of rural and urban poor people, especially women (Njenga et al 2013a;Bennett et al 2018;Sola et al 2019;Ndegwa et al 2020). COVID-19 has put at risk the nutrition and incomes of millions of people, especially in some countries in sub-Saharan Africa, such as the Democratic Republic of Congo, by disrupting supply chains for charcoal (Schure et al 2021b).…”
Section: Value Chainsmentioning
confidence: 99%